The Greatest Defender of Truth shall Remain in the eye of a Poet (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
It has been created within the larger realm culture, in that "Black methodology differs from mostcolonialdifferences by members of a minority community who reside within a nation of cultural biases."